Molecular characterization and phylogenetic analysis of Bacillus pumilus causing trunk bulges of RRIM 3001 superclone rubber tree in Malaysia - Mazlan, Safwan; Md Jaafar, Noraini; Wahab, Aswad; Sulaiman, Zulkefly; Rajandas, Heraa; Zulperi, Dzarifah (Springer Dordrecht, 2021)
Hevea brasiliensis (rubber tree) is well known as the tree of life for its by-products such as wood and latex. The introduction of super clones with high yield potential such as RRIM 3001 is among the efforts to improve latex and timber yields. However, the RRIM 3001 super clone is prone to a disease known as trunk bulges. The appearing of bulging on the tapping panel causes difficulties during the tapping process for harvesting the latex and affects the quality of wood produced. In this study, we aimed to characterize Bacillus pumilus (B. pumilus) causing trunk bulges disease of RRIM 3001 super clone rubber tree isolated from the infected rubber trees in Malaysia. During October to December 2017, samples with trunk bulges symptoms were collected from four rubber plantations with reported outbreaks. Ten bacterial isolates from vascular tissues of rubber tree with trunk bulges symptom were confirmed as Bacillus pumilus species by the production of yellow pigmentation, circular, raised and entire form colonies on Bacillus differentiation agar medium. All of the isolates are Gram-positive, rod-shaped, motile, as well as endospores formers. They were positive for catalase activities and negative in both potassium hydroxide (KOH) and sulfide productions. All bacterial isolates utilized glucose, inositol, mannitol, sucrose, xylose and trehalose, but did not utilize lactose and arabinose. Application of 16S rRNA, species-specific primers; Bsub5F/Bsub3R and UP-1S/UP-2Sr (GyrB gene) successfully identified all isolates as B. pumilus. Phylogenetic analysis of both genes further clustered these isolates into the same cluster to a B. pumilus reference strain in the GenBank database (GenBank Accession Nos. KF158227 and MF968898). The results from this study are useful for developing management strategies of B. pumilus in rubber plantations, since rubber tree has been recognized as important commodity crop with high economic value in Malaysia.